Predictive Policing: Current and Future Policing - Harry Seldadyo; Eko Rudi Sudarto; Ahrie Sonta (Budapest International Research and Critics University, 2022)
In the era when everything is moved by data, policing efforts are necessary and important for self-adaptation. Predictive policing is in these dynamics of data-based policing to do prediction and to take the action which can change certain outcome to the expected result. Nevertheless, the existing literature usually discuss predictive policing in technical micro dimension. This writing fulfils the gap which has smaller attention from the literature that is the discussion on each meso and micro dimension which has tactical and strategical characteristics. As a result, the complete and integrative perspectives can be contributed to discourse of predictive policing.